Carpal Tunnel Syndrome: A cross - Sectional Study in 928 Patients in Iraq - Abbas , Hikmet kadum (Diyala Journal of Medicine, 2019)
Background: Carpal tunnel syndrome is caused by entrapment of the median nerve and results in pain, tingling and numbness in the wrist and hand. It is a common condition in general practice. Aim: This study was done to determine the epidemiological and clinical features of CTS. Methods A cross-sectional study was carried out on Carpal tunnel syndrome [CTS] cases diagnosed over a 14 years period, from May 1998 to May 2012 by the researcher. All data regarding the age at presentation, gender, pregnancy, hypertension, DM, salty food, response to conservative treatment, response to surgical treatment, a total number of 928 cases were included in this study. Results; Among the 928 CTS patients; there were (0.107%) below 15 years,( 25.64%) from 15-30 years, (50.75%) from 31-45 years, (20.68%) from 46-60 years, and (2.80%) above 60.According to gender distribution, there were (0.969%) male,( 99.03%) female. In this study there were (13.27%) pregnant,( 86.72%) not pregnant, (5.92%) hypertensive,( 94.07%) not hypertensive, (8.40 %) diabetic,( 91.59%) not diabetic, (44.40%) eating salty food, (55.60%) not eating salty food .According to response to treatment, (58.72%) respond to conservative treatment,( 41.27%) not respond to conservative treatment, (94.51%) good response to surgical treatment,( 5.48%) not respond to surgical treatment. Conclusions: This study showed The predominant age of patients [females] 31-45 years. The ratio of female /male is far higher than in other places of the world. The prevalence of pregnant women with CTS is less than other studies. There is some statistical significant association between CTS and consuming salty food. Surgical treatment is highly successful.